8-5p=-6p-8+6

Simple and best practice solution for 8-5p=-6p-8+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-5p=-6p-8+6 equation:



8-5p=-6p-8+6
We move all terms to the left:
8-5p-(-6p-8+6)=0
We add all the numbers together, and all the variables
-5p-(-6p-2)+8=0
We get rid of parentheses
-5p+6p+2+8=0
We add all the numbers together, and all the variables
p+10=0
We move all terms containing p to the left, all other terms to the right
p=-10

See similar equations:

| 8k-6=6(k+3+6k | | 5-3(w+4)=w-19 | | 3.2-16=a | | 5x+-5.2=9.4+3x | | 7+7u=4+6u | | 6-(4x-7)=6-5x | | -4+y/5=9 | | 2+2z=7z-8 | | 8(x+3)=-16 | | -9-u=7-5u | | 5y^2+44y+46=0 | | 20-8x=15=x | | 360=35+35+x+x | | -3=12y-512y-7 | | -2-9w=-8w | | 2x+3x-1=5x-1 | | .08x+x=252 | | 2.5x-8=1.5x+1 | | 7f=8+8f | | 5=-2-(1/x) | | 8r+2=72+r | | 13+6t=9 | | -8r=-10-7r | | 5g=6g-7 | | 6y+22=3y+49 | | 12r+12=3r+84 | | 12x+4x-9=9x+7-5x | | 3a-5=a-7 | | -x+4+3x=2x | | 9x-x+2=10 | | -5z-9=6z | | 5+8(x+8)=69-12(3x+11) |

Equations solver categories